2005
DOI: 10.1002/app.22629
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic investigations on the UV‐induced photopolymerization of nanocomposites by FTIR spectroscopy

Abstract: ABSTRACT:The kinetics of the photopolymerization for nanocomposites containing nanosilica with 2,2-dimethoxy-1,2-diphenylethan-1-one or benzophenone/n-methyl diethanolamine (BP/MDEA)as photoinitiators were studied by FTIR spectroscopy. It was found that nanocomposites containing nanosilica had higher conversion in comparison with pristine EA. The presence of MPS and ethanol accelerated the photopolymerization of nanocomposites, while the presence of water decelerated it. The photopolymerization of nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…[22] In other studies, silica nanoparticles have resulted in an increase the rate of polymerization which has been attributed to changes in propagation and termination rate constants. [23][24][25] Also, modified nanoparticles as multifunctional sites form a three-dimensional network which leads to reduction in the mobility of chains and thus slow down the rate of polymerization. [24][25] Due to the formation of aggregates, greater particle size leads to higher rate of reaction, which is mainly because of high medium viscosity and the occurrence of auto-acceleration phenomenon.…”
Section: Polymerization Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] In other studies, silica nanoparticles have resulted in an increase the rate of polymerization which has been attributed to changes in propagation and termination rate constants. [23][24][25] Also, modified nanoparticles as multifunctional sites form a three-dimensional network which leads to reduction in the mobility of chains and thus slow down the rate of polymerization. [24][25] Due to the formation of aggregates, greater particle size leads to higher rate of reaction, which is mainly because of high medium viscosity and the occurrence of auto-acceleration phenomenon.…”
Section: Polymerization Kineticsmentioning
confidence: 99%
“…[23][24][25] Also, modified nanoparticles as multifunctional sites form a three-dimensional network which leads to reduction in the mobility of chains and thus slow down the rate of polymerization. [24][25] Due to the formation of aggregates, greater particle size leads to higher rate of reaction, which is mainly because of high medium viscosity and the occurrence of auto-acceleration phenomenon. [24][25] On the other hand, in some studies, an optimum loading of silica nanoparticles has been reported in which the polymerization rate reaches the maximum value.…”
Section: Polymerization Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al [14] embedded MPS-modified ZnO nanoparticles into polyurethane acrylate oligomer and 2-hydroxyethylmethacrylate. Li et al [15][16][17] introduced MPS-modified silica nanoparticles into the mixture of trimethylolpropane triacrylate (TMPTA) and epoxy acrylate or into MPS itself. Landry et al [18] embedded MPSfunctionalized alumina or zirconia (ZrO 2 ) nanoparticles into a UV-curable formulation which was consisted of two monomers and two oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…Photopolymerization kinetics of (meth)acrylate monomers containing dispersed nanosilica were considered in several papers and various dependences of the polymerization rate and conversion on silica content were obtained; the results were explained in various ways [9][10][11][12]. Ours previous papers [8,13,14] analyzed kinetics more deeply (in the considered cases a maximum on the dependence of the polymerization rate on the silica content was observed).…”
Section: Introductionmentioning
confidence: 99%